Respuesta :
if you're looking for f(x)
then
g(x) = sqrt(4x + 4)
h(x) = sqrt(4x + 28)
h(x)-g(x) = 24
meaning that sqrt(24) must be the constant of f(x)
f(x) = x(sqrt(24))
h(x) = f(g(x)) = (sqrt(24))(sqrt(4x+4)) = sqrt(4x+4+24) = sqrt(4x+28)
then
g(x) = sqrt(4x + 4)
h(x) = sqrt(4x + 28)
h(x)-g(x) = 24
meaning that sqrt(24) must be the constant of f(x)
f(x) = x(sqrt(24))
h(x) = f(g(x)) = (sqrt(24))(sqrt(4x+4)) = sqrt(4x+4+24) = sqrt(4x+28)
Answer:
[tex]f(x) = \sqrt[4]{x+6}[/tex]
Step-by-step explanation:
Let [tex]h(x) = \sqrt[4]{x+7}[/tex] and [tex]g(x) = \sqrt[4]{x+1}[/tex]. By some algebraic handling:
[tex]h(x) = \sqrt[4]{(x+1)+6}[/tex]
[tex]h(x) = \sqrt[4]{(\sqrt[4]{x+1} )^{4}+6}[/tex]
But [tex]g(x) = \sqrt[4]{x+1}[/tex]. Therefore:
[tex]f(x) = \sqrt[4]{x+6}[/tex]